Signs of skin aging: a review - Fernández-Varela-Gómez, Fernando; Sandoval-García, Alicia; Valeria Cabrera-Rios, Karla (International Journal of Research in Medical Sciences, 2024)
Skin aging is a complex process affected by both internal and external factors, leading to changes in skin structure and function. The connection between signs of skin aging and age is intricate, involving genetic, environmental, and lifestyle influences. However, relying solely on chronological age fails to accurately predict skin aging due to the complex interplay of these factors. Interventions such as retinoids show promise in altering skin aging processes, questioning the exclusive use of chronological age for predictions. Skin aging goes beyond appearance, reflecting deeper changes in skin function and structure. Therefore, comprehensive strategies including sun protection and topical treatments are essential for managing aging effects. In essence, understanding the intricate nature of skin aging and adopting holistic approaches tailored to individual factors are vital for promoting skin health throughout life.